Ultra‐early continuous cardiac monitoring improves atrial fibrillation detection and prognosis of patients with cryptogenic stroke. (18th September 2019) - Cuadrado‐Godia, E.; Benito, B.; Ois, A.; Vallès, E.; Rodríguez‐Campello, A.; Giralt‐Steinhauer, E.; Cabrera, S.; Alcalde, O.; Jiménez‐López, J.; Jiménez‐Conde, J.; Martí‐Almor, J.; Roquer, J.
Abstract : Background and purpose: Subclinical atrial fibrillation (AF) is known to underlie a number of cases of cryptogenic stroke (CrS). However, there is need to define the most effective strategy for AF detection. The diagnostic usefulness was analysed of a strategy based on ultra‐early continuous monitoring in patients with CrS in terms of AF detection, oral anticoagulation treatment and stroke recurrence, in comparison to a standard outpatient strategy. Methods: Patients with ischaemic stroke of undetermined origin and confirmed to be cryptogenic after extensive work‐up were searched for AF with (i) a conventional strategy (historical cohort, n = 101) with serial electrocardiograms and 24‐h Holter monitoring or (ii) an ultra‐early monitoring strategy with insertable cardiac monitor (ICM) implanted before discharge (prospective cohort, n = 90). AF episodes lasting >1 min, anticoagulant treatment and stroke recurrence were recorded. Results: During admission, AF was similarly detected in both cohorts (24% of patients). After discharge (mean follow‐up 30 ± 10 months), AF detection rates were 17/80 (21.3%) and 38/65 (58.5%) for patients in the conventional versus the ultra‐early ICM group ( P < 0.001). Up to 41% of AF cases in the ICM cohort were detected within the first month. Oral anticoagulation was initiated in 37.6% versus 65.5% ( P < 0.001) and stroke recurrence was recorded in 10.9% versus 3.3% ( P 0.04) in the conventional versus the ICM cohort. Conclusions: Pre‐discharge ICM implant allows detection of AF during follow‐up in up to 58% of selected patients with CrS. Compared to a conventional strategy, ultra‐early ICM implant results in higher anticoagulation rates and a decrease in stroke recurrence.